COMPARISON OF TWO TYPES EYE LENS DOSEMETERS USED IN INTERVENTIONAL CARDIOLOGY AND RADIOLOGY - Martinčík, Jiří; Čechák, Tomáš; Urban, Tomáš; Tamášová, Jana; Siková, Lenka; Jakubcová, Iva; Balogová, Zdenka (Radiation protection dosimetry, 2022)
The aim of this contribution is to provide an overview of comparison of two types of eye lens dosemeter systems. The comparison was performed at the Department of Intravenous Cardiology using patient and physician phantoms and supplemented by dose simulation using the Monte Carlo method. The tests were performed in several specific geometries and in addition to eye lens dosemeters the value of a personal dosemeter located at the reference point was also monitored. The value of Hp(3) and Hp(10) was monitored. It is clear from the results that film dosemeters achieve more correct results in most cases. It is probably due to a better correction for the angle of exposure. This assumption must be verified by more detailed measurements in laboratory conditions.
Keywords: Cardiology; oční čočka; Lens, Crystalline; Radiation Protection; lidé; Radiology, Interventional; kardiologie; pracovní expozice; Radiation Dosage; intervenční radiologie; Humans; dávka záření; radiační ochrana; Occupational Exposure